Hunger Quits School - United States. Food Distribution Administration (1943)
Hunger Quits School is a pamphlet published in 1943 by the United States Food Distribution Administration. This pamphlet explains the benefits of school lunch programs, and how to start them in local communities. When the Food Distribution Administration was created by executive order in December 1942, it took over responsibility for the school lunch program (formerly managed by the Agricultural Marketing Administration), which had been created after almost a quarter of men were turned away from serving in the U.S. military due to malnutrition. The Food Distribution Administration was consolidated with other agencies and became, in April 1943, the War Food Administration, responsible for managing the production and distribution of food to civilians during World War I. These efforts inspired the advancement of nutritional research and education for the American people. In 1946 the United States passed the National School Lunch Act which provides free or low-cost lunches to qualifying students.
Keywords: School children--Food; National school lunch program; United States. Food Distribution Administration